Effect of high fat diet on structure of liver and gallbladder of adult male mice – an experimental study - Hegazy, Abdelmonem Awad; Qenawy, Noura M.; Aziz, Nada M. Abdel; El-Bestawy, Emtethal M. (European Journal of Clinical and Experimental Medicine, 2021)
<h2 class="block-title" style="box-sizing: border-box; font-family: Lato, sans-serif; font-weight: bold; line-height: 1.1; color: #010101; margin-top: 23px; margin-bottom: 11.5px; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Abstract <div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Introduction. High fat diet (HFD) intake induces obesity and adversely affects different body organs including liver and gallbladder. Aim. It was to clarify the effects of HFD on the liver and gallbladder structure using light microscopic (LM) examination. Material and methods. 16 healthy adult male mice were equally divided into 2 groups. Control group mice were fed normal diet. HFD group was fed using HFD. At the end of the 8-week experiment, mice were anesthetized. Liver and gallbladder were removed and prepared to histological processing. Sections were stained with hematoxylin and eosin (H&E) and immunostaining for cyclooxygenase-2 (COX-2) cellular localization. Oil Red O (ORO)-stained frozen liver sections were prepared. Results. H&E-stained sections of HFD group revealed rounded swollen hepatic cells with pale cytoplasm suggesting cellular ballooning. Dilated congested sinusoids and portal vein, cellular degeneration and collection of inflammatory cells were observed between hepatic cells and in portal region. Gallbladder sections showed epithelial stratification and cellular vacuolation. Strong immunoexpression of COX-2 was observed in Kupffer and hepatic cells of the liver and gallbladder mucosal epithelial cells. Conclusion. HFD is suggested to alter the normal histological features of liver and gallbladder represented by fatty liver and gallbladder epithelial hyperplasia and inflammatory reaction.